Prevalence of functional constipation and its associated factors among elderly patients in Hospital Universiti Sains Malaysia - Mohamad, Nurul Izaa (2017)
Introduction: Functional constipation (FC) is a common functional gastrointestinal disorder (FGID). The prevalence of this disease depends on the methodology of the study and geographical area. Constipation can cause medical complications and psychological impact if left untreated. Objectives: The aim of this study is to determine the prevalence of functional constipation and its associated factors among elderly attending the outpatient clinic in Hospital Universiti Sains Malaysia (HUSM). Besides that, stool consistency and frequency of bowel movement among those with constipation will be described. Methodology: A cross-sectional study involving 237 elderly patients aged ≥ 60years old who attended the outpatient clinic at HUSM from 1st December 2015 to 1st March 2016 was carried out via multistage and systematic random sampling. A validated self-administered Rome III functional constipation (Bahasa Malaysia version) questionnaire, which underwent test-retest reliability in a 14 days interval, had a Cronbach alpha of 0.88 and inter-class correlation (ICC) of 0.88 (95% 0.84,0.91) was given to every patient. Another part of the questionnaire included sociodemographic, lifestyle, disease, medication and stool diary recall to assess the frequency of bowel movement (BM) in a week and stool consistency. Result: The prevalence of functional constipation among elderly is 13.5% (95% CI: 9.5, 17.5). This study found that elderly patients with constipation (81.3%) had bowel movementmore than 3 times per week ( ≥3/weeks) with a mean (SD) for bowel movement of 3.25 (1.02). These patients had more Type 1 stool (65.6%) compared to those without constipation (10.7%). Likewise, for Type 2 it was, (34.4%) vs ( 5.9%) and for Type 3 it was (46.9%) vs (26.8%). Multivariate analysis demonstrated that age (adj.OR1.08,95%CI:1.02,1.14; p=0.010) and plain water intake (adj OR 0.81, 95% CI: 0.67,0.97; p=0.025) are significantly associated with functional constipation. Conclusion: The prevalence of functional constipation among elderly in this study is 13.5% and many of them had bowel movement more than three times per week with stool Types 1 to 3. Age and plain water intake are found to be significantly associated with functional constipation.